Discovery and Characterization of a Biologically Active Non–ATP-Competitive p38 MAP Kinase Inhibitor - Wilson, Brice A. P. (J Biomol Screen, 2015)
Mitogen-activated protein kinase (MAPK) p38 is part of a broad and ubiquitously expressed family of MAPKs whose activity is responsible for mediating an intracellular response to extracellular stimuli through a phosphorylation cascade. p38 is central to this signaling node and is activated by upstream kinases while being responsible for activating downstream kinases and transcription factors via phosphorylation. Dysregulated p38 activity is associated with numerous autoimmune disorders and has been implicated in the progression of several types of cancer. A number of p38 inhibitors have been tested in clinical trials, with none receiving regulatory approval. One characteristic shared by all of the compounds that failed clinical trials is that they are all adenosine triphosphate (ATP)–competitive p38 inhibitors. Seeing this lack of mechanistic diversity as an opportunity, we screened ~32,000 substances in search of novel p38 inhibitors. Among the inhibitors discovered is a compound that is both non–ATP competitive and biologically active in cell-based models for p38 activity. This is the first reported discovery of a non–ATP-competitive p38 inhibitor that is active in cells and, as such, may enable new pharmacophore designs for both therapeutic and basic research to better understand and exploit non–ATP-competitive inhibitors of p38 activity.